Correlation Between Motor Coordination and Running Speed with Hurdle Running Ability in Students of SMAN 5 Binjai City - Farid M. Alhumary; Faldin Sejahtera Halawa; Joniman Zega; Septerlima Harefa; Valenti Putra Jaya Gulo (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: Hurdle running is a complex athletic discipline requiring optimal coordination between motor skills and running velocity. This study investigates the relationship between motor coordination, running speed, and hurdle running performance in high school students. To examine the correlation between motor coordination and running speed with hurdle running ability in students of SMAN 5 Binjai City, North Sumatra, Indonesia. Methods: This correlational study involved 40 high school students (aged 15-18 years) from SMAN 5 Binjai City. Motor coordination was assessed using standardized coordination tests, running speed was measured through sprint performance evaluations, and hurdle running ability was evaluated using specific hurdle clearance assessments. Results: Strong positive correlations were found between motor coordination and hurdle performance (r = 0.807, p < 0.001), running speed and hurdle performance (r = 0.869, p < 0.001), and motor coordination and running speed (r = 0.756, p < 0.001). Motor coordination scores averaged 71.59 ± 12.80, running speed scores 81.23 ± 10.14, and hurdle performance scores 85.83 ± 8.69. Conclusion: Motor coordination and running speed significantly correlate with hurdle running ability, with running speed showing the strongest relationship. These findings support the importance of developing both coordination skills and sprint capacity for optimal hurdle performance in high school athletes.